2008
DOI: 10.1037/0894-4105.22.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Identical neural risk factors predict cognitive deficit in dyslexia and schizophrenia.

Abstract: In previous work, the authors found that an anatomical risk index created from the combination of 7 neuroanatomical measures predicted reading and oral language skills in individuals with learning disabilities. Individuals with small auditory brain structures and reduced asymmetry had more deficits than those with large structures and exaggerated asymmetry. In the present study, the same anatomical index predicted reading and other cognitive abilities in 45 individuals with chronic schizophrenia. The anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…A key methodological difference is whether cortical surface or volume was measured. Several of the studies that did not report asymmetry reductions in patients used PT surface (e.g., Kleinschmidt et al, 1994;Kulynych et al, 1995;Leonard et al, 2008), rather than the volume measures used in the present study, although a few studies found reduced or reversed asymmetry with surface measures as well . Some of the earlier volumetric studies used rather coarse tessellations of the regions of interest (e.g., square grids with several millimeters of spacing) , which may have resulted in overestimations of cortical volume and made the method less sensitive.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A key methodological difference is whether cortical surface or volume was measured. Several of the studies that did not report asymmetry reductions in patients used PT surface (e.g., Kleinschmidt et al, 1994;Kulynych et al, 1995;Leonard et al, 2008), rather than the volume measures used in the present study, although a few studies found reduced or reversed asymmetry with surface measures as well . Some of the earlier volumetric studies used rather coarse tessellations of the regions of interest (e.g., square grids with several millimeters of spacing) , which may have resulted in overestimations of cortical volume and made the method less sensitive.…”
Section: Discussionmentioning
confidence: 72%
“…Alternative diagnostic approaches, for example based on endophenotypes, may be useful for future investigations to further restrict the inherent heterogeneity of symptoms and syndromes within schizophrenia (Gottesman and Gould, 2003;Braff et al, 2007). Another moot case is whether reduced temporal lobe asymmetry, if it exists, is specifically associated with schizophrenia or rather with cognitive impairment and poor coping abilities, as suggested by Leonard et al (2008). Our findings in relatives would support a specific association with schizophrenia risk, although they do not rule out that altered asymmetry is also an independent risk factor for language or other cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, functional imaging studies show cerebellar engagement during reading tasks (e.g., Turkeltaub et al, 2002; reviewed in Stoodley and Stein, 2011) and a magnetoencephalography study by Kujala et al (2007) indicated that the cerebellum was one of the forward-driving nodes in the reading network. Structural differences in the cerebellum have been reported in dyslexia (e.g., Eckert, 2004), including differences in symmetry (with dyslexic individuals showing less-asymmetric cerebella than their TD counterparts, who generally show a rightward cerebellar asymmetry; Rae et al, 2002; Kibby et al, 2008; Leonard et al, 2008). Pernet et al (2009) reported that a region in right lobule VI was the most significant biomarker for classification of adult dyslexic brains.…”
Section: Introductionmentioning
confidence: 99%
“…A recent structural MRI (sMRI) study linked these difficulties to structural abnormalities in language-related regions (Leonard et al, 2008). Similar regions have been implicated in primary reading disability (RD).…”
mentioning
confidence: 99%